A revista civilização brasileira: projeto editorial e resistência cultural (1965-1968) - Czajka, Rodrigo (Universidade Federal do Paraná, 2010)
During the first years of the military dictatorship, established in Brazil through a coup d'État, a number of institutions which repression had left unarticulated began a process of resistance and opposition to the military government. Cultural resistance was one of the consecrated forms of resistance that was exercised by intellectuals, artists, professors and cultural producers, among others, and that became an unprecedented political and cultural phenomenon in the country's history. Political, insofar as it aided in the process of re-organizing left-wing political parties and in the revision of the ideological postulates of its preeminent party, the PCB (Partido Comunista Brasileiro - Brazilian Communist Party). Cultural, because this re-organization occurred, frequently, within the ambit of cultural productions, in which the left created a space for contestation and engagement through the arts and intellectual activities. Within this process, between the years 1965 and 1968. The journal Civilização Brasileira became an important space for the building of leftist cultural resistance against the military dictatorship. The journal was able to impose its political legitimacy while at the same time participating actively in a market o cultural goods sustained by the so-called cultural hegemony of the left.

Dans les premières années de la dictature militaire, instaurée au Brésil, en 1964, par un coup d'État, plusieurs institutions dispersées par la répression ont commencé un processus de résistance et d'opposition au régime militaire. La résistance culturelle a été l'un des moyens consacrés de résistance chez les intellectuels, artistes, enseignants, producteurs culturels, entre autres, et qui a aussi été un phénomène culturel et politique sans précédent dans l'histoire du Brésil. Politique, parce qu'il a mis en oeuvre la réorganisation des partis de gauche et la révision des postulats idéologiques de leur parti de premier plan, le Parti communiste brésilien. Culturel, parce que cette réorganisation a eu lieu souvent dans le cadre des productions culturelles, dans lequel la gauche a créé un espace de contestation et d'engagement par le biais des arts et des activités intellectuelles. C'est au cours de ce processus que le magazine Civilisation Brésilienne a représenté un espace important pour la construction de cette résistance culturelle de gauche contre la dictature militaire, entre les années 1965 et 1968. La revue s'est imposée avec une légitimité politique tout en participant activement à la formation d'un marché pour les biens culturels soutenu par ce qu'on appelle l'hégémonie culturelle de gauche.

Nos primeiros anos da ditadura militar, instaurada no Brasil em 1964 por meio de um golpe de Estado, diversas instituições desarticuladas pela repressão iniciaram um processo de resistência e oposição ao governo militar. A resistência cultural foi uma das formas consagradas de oposição exercida por intelectuais, artistas, professores, produtores culturais, entre outros, e que consistiu num fenômeno político e cultural sem precedentes na história do Brasil. Político, porque auxiliou no processo de reorganização dos partidos de esquerda e na revisão dos postulados ideológicos do seu partido proeminente, o Partido Comunista Brasileiro. Cultural, porque essa reorganização deu-se, muitas vezes, no âmbito das produções culturais, no qual a esquerdas constituíram um espaço de contestação e engajamento através das artes e das atividades intelectuais. Nesse processo é que a Revista Civilização Brasileira representou um espaço importante para a construção dessa resistência cultural de esquerda contra a ditadura militar, entre os anos de 1965 e 1968. A revista impôs-se com legitimidade política, ao mesmo tempo em que participou ativamente na formação de um mercado de bens culturais sustentado pela chamada hegemonia cultural de esquerda.
The journal revista civilização brasileira: editorial project and cultural resistence (1965-1968)
La revue civilização brasileira: projet d'édition et résistance culturelle (1965-1968)
Keywords: imprensa comunista; intelectuais de esquerda; resistência cultural; ditadura militar; communist press; leftist intellectuals; cultural resistance; military dictatorship